2020
DOI: 10.14202/ijoh.2020.128-133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sauropus androgynus extract and its combination with ampicillin against Methicillin-resistant Staphylococcus aureus: An in vitro study

Abstract: Background and Aim: The massive utilization of antibiotics has increased resistant genes produced by bacteria. Many bacteria, including Methicillin-resistant Staphylococcus aureus (MRSA), have become resistant against ampicillin (AMP). The combination of an herbal extract with AMP is expected to generate synergistic effects and may restore the susceptibility of MRSA against AMP. This study aimed to analyze the potency of Sauropus androgynous extract (SAE) as a single extract and combination with AMP against MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Interestingly, the extract S. androgynus shows antibacterial activity against antibiotic-resistant bacteria such as Staphylococcus aureus AMR strain. Rahayu et al [ 192 ] demonstrated the antibacterial activity of the 60% ethanol extract of S. androgynus against methicillin-resistant, ampicillin-resistant Staphylococcus aureus strain. Bioactive components such as phenolics and flavonoids cause ultrastructural changes in the bacterial membrane which result in their growth reduction.…”
Section: Pharmacology Of Sauropus Androgynusmentioning
confidence: 99%
“…Interestingly, the extract S. androgynus shows antibacterial activity against antibiotic-resistant bacteria such as Staphylococcus aureus AMR strain. Rahayu et al [ 192 ] demonstrated the antibacterial activity of the 60% ethanol extract of S. androgynus against methicillin-resistant, ampicillin-resistant Staphylococcus aureus strain. Bioactive components such as phenolics and flavonoids cause ultrastructural changes in the bacterial membrane which result in their growth reduction.…”
Section: Pharmacology Of Sauropus Androgynusmentioning
confidence: 99%